1997
DOI: 10.2118/35412-pa
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Transformations for Multiple Regression: Application to Permeability Estimation From Well Logs

Abstract: Conventional multiple regression for permeability estimation from well logs requires a functional relationship to be presumed. Because of the inexact nature of the relationship between petrophysical variables, it is not always possible to identify the underlying functional form between dependent and independent variables in advance. When large variations in petrological properties are exhibited, parametric regression often fails or leads to unstable and erroneous results, especially for multivariate cases.In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 6 publications
0
51
0
Order By: Relevance
“…These algorithms include multiple linear regression (Dahraj and Bhutto 2014;Mohaghegh et al 1997;Xue et al 1997), generalized additive modeling (Al-Mudhafar and Mohamed 2015; AlMudhafar and Bondarenko 2015; Lee et al 2002;Rafik and Kamel 2016), multivariate adaptive regression splines (Al-Mudhafar and Al-Khazraji 2016;Xie 2008), neural networks (Lee and Datta-Gupta 1999;Lee et al 2002;Mohaghegh et al 1997), fuzzy logic (Nashawi and Malallah 2009), and support vector regression (Al-Anazi and Gates 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These algorithms include multiple linear regression (Dahraj and Bhutto 2014;Mohaghegh et al 1997;Xue et al 1997), generalized additive modeling (Al-Mudhafar and Mohamed 2015; AlMudhafar and Bondarenko 2015; Lee et al 2002;Rafik and Kamel 2016), multivariate adaptive regression splines (Al-Mudhafar and Al-Khazraji 2016;Xie 2008), neural networks (Lee and Datta-Gupta 1999;Lee et al 2002;Mohaghegh et al 1997), fuzzy logic (Nashawi and Malallah 2009), and support vector regression (Al-Anazi and Gates 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Neural Network modeling can be considered as one of the nonparametric modeling approaches and has wide range of applications in oil industry. However, the method that was used here is based on the Alternating Conditional Expectation (ACE) algorithm [26,27]. A comparison between Neural Network and ACE algorithm was used to build bubble point pressure correlation for oil reservoirs [28] and it was found that the predictive strength of ACE is much higher compared to Neural Network for the studied samples.…”
Section: Non-parametric Regression Analysismentioning
confidence: 99%
“…(20). The 550 several combinations of the 9 sensitive parameters which represent the independent variables with one dependent variable that is C 1 were used in the ACE Algorithm [27] to find the best correlation between the dependent and the independent variables. The resulted IPR correlation is given in Eq.…”
Section: Non-parametric Regression Analysismentioning
confidence: 99%
“…It can be applied both in bivariate and multivariate cases and it yields maximum correlations in transformed space (Malallah et al, 2006). A modification of ACE algorithm with graphical (GRACE) interface was later proposed by Xue et al (1997).…”
Section: Alternating Conditional Expectations (Ace)mentioning
confidence: 99%